Aptinothrips iraniensis sp. n. (Thysanoptera, Thripidae) with a key to the four Aptinothrips species known from Iran - Alavi, Jalil (Zootaxa, 2020)
Aptinothrips iraniensis sp. n. is described from northeast of Iran as the fifth species in this genus. It is closely similar to A. rufus in shape and habitat. An illustrated key is provided to the four species of Aptinothrips recorded from Iran.